Hyperbolic Optical Metamaterials from Shear‐Aligned Block Copolymer Cylinder Arrays. Issue 2 (4th November 2020) - Kilchoer, Cédric; Abdelrahman, Doha; Abdollahi, S. Narjes; LaRocca, Ava A.; Steiner, Ullrich; Saba, Matthias; Gunkel, Ilja; Wilts, Bodo D.
Abstract : Hyperbolic metamaterials behave similarly to either metals or dielectrics depending on the polarization of incident light. This behavior is reflected in permittivity tensors having both negative and positive components, which leads to interesting optics such as negative refraction and super‐resolution imaging. To achieve this polarization‐dependent electromagnetic response, hyperbolic metamaterials require a strongly anisotropic nanostructure made from noble metals. Herein, a nanostructured array of aligned gold and silver nanocylinders that exhibit a strongly anisotropic optical response both in reflection and transmission are investigated. The plasmonic material is manufactured using films of aligned block copolymer (BCP) cylinders as template, where a uniform alignment is achieved by annealing in the presence of an external shear force. Metal deposition into a nanoporous polymer template resulted in free‐standing metal nanostructures consisting of a hexagonally packed in‐plane cylinder array supported by occasional interconnections between adjacent cylinders. 3D full‐wave simulations confirm the experimentally measured anisotropic response of the metallic nanocylinders and show that the interconnections between cylinders affect the optical response while maintaining the hyperbolic nature of the metamaterial. The large‐scale alignment of anisotropic BCP nanostructures provides useful templates for the fabrication of metal‐based optical materials with potential applications as polarizers, sensors, or angle‐dependent broadband absorbers. Abstract : Hyperbolic optical metamaterials consisting of an array of aligned gold or silver nanocylinders are produced from shear‐aligned block copolymer templates via electrochemical deposition. The hyperbolic response can be tuned by selecting different metals and is uniform over macroscopically large areas. Computational simulations confirm the hyperbolic response of the manufactured metamaterials.